Encyclopedia of Human Evolution and Prehistory - Delson, Eric; Tattersall, Ian; Van Couvering, John; Brooks, Alison S. (Taylor & Francis, 2000)
Praise for the first edition: "The most up-to-date and wide-ranging encyclopedia work on human evolution available."--American Reference Books Annual "For student, researcher, and teacher...the most complete source of basic information on the subject."--Nature "A comprehensive and authoritative source, filling a unique niche...essential to academic libraries...important for large public libraries." --Booklist/RBB